2004
DOI: 10.2193/0091-7648(2004)032[0627:acoeor]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of effects of radiotransmitter attachment techniques on captive white-winged doves

Abstract: We experimentally evaluated alternative techniques of attaching radiotransmitters to captive white-winged doves (Zenaida asiatica) in Kingsville, Texas during 1998. Our evaluation consisted of monitoring physiological, pathological, and behavioral parameters in doves subjected to 6 radiotransmitter attachments (backpack harnesses, adhesive, subcutaneous implants, intracoelomic implants, subcutaneous surgeries without implantation, intracoelomic surgeries without implantation). We analyzed physiological paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 32 publications
(39 reference statements)
3
50
1
Order By: Relevance
“…In our study, although the skin incision was totally clean and completely healed before device recovery, a fibrous capsule was found around the loggers indicating the occurrence of an inflammatory response (Anderson et al 2008). However, the presence of this capsule has not been associated with physiological or behavioural deleterious effects in previous studies (Small et al 2004;Mulcahy et al 2007). A more probable reason of the extended recovery surface intervals is that the device (volume: *20 cm 3 ) may have pressurised adjacent organs such as air sacs (Small et al 2004), thus reducing the birds' efficiency to ventilate at the surface.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…In our study, although the skin incision was totally clean and completely healed before device recovery, a fibrous capsule was found around the loggers indicating the occurrence of an inflammatory response (Anderson et al 2008). However, the presence of this capsule has not been associated with physiological or behavioural deleterious effects in previous studies (Small et al 2004;Mulcahy et al 2007). A more probable reason of the extended recovery surface intervals is that the device (volume: *20 cm 3 ) may have pressurised adjacent organs such as air sacs (Small et al 2004), thus reducing the birds' efficiency to ventilate at the surface.…”
Section: Discussioncontrasting
confidence: 48%
“…However, the presence of this capsule has not been associated with physiological or behavioural deleterious effects in previous studies (Small et al 2004;Mulcahy et al 2007). A more probable reason of the extended recovery surface intervals is that the device (volume: *20 cm 3 ) may have pressurised adjacent organs such as air sacs (Small et al 2004), thus reducing the birds' efficiency to ventilate at the surface. Culik and Wilson (1991) found that the cost of transport of implanted Adélie penguins swimming in a water canal was lower than that of externally-equipped penguins (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of such studies indicate that transmitters may (Foster et al 1992, Mattson et al 2006) or may not (Hernandez et al 2004, Sunde 2006) have a negative impact on birds. More recently, investigators have examined possible adverse physiological effects of transmitters, such as increased stress levels (Schulz et al 2001, Small et al 2004, Schulz et al 2005, Small et al 2005) that could affect behavior, longevity, and reproduction, and have found little evidence of such effects. However, these studies were limited to birds in captivity and may not reflect conditions faced by wild birds, especially during potentially stressful parts of their life cycles.…”
mentioning
confidence: 99%
“…A subcutaneous VHF transmitter was, however, recently tested with Bornean (Pongo pygmaeus) (Walzer et al 2010) and Sumatran orang-utans (Pongo abelii). Other implants, although subcutaneous, have often had external antennae (Echols et al 2004;Iverson et al 2006;Mulcahy & Garner 1999;Small et al 2004), making them impractical for use with primates, but this implant has no external component. It is implanted dorsally in the neck of the orang-utan (Pongo sp.)…”
Section: Introductionmentioning
confidence: 99%